Benefits of Continuous Subcutaneous Insulin Infusion (CSII) Therapy in Preschool Children - Levy-Shraga, Y.; Lerner-Geva, L.; Modan-Moses, D.; Graph-Barel, C.; Mazor-Aronovitch, K.; Boyko, V.; Pinhas-Hamiel, O. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The incidence of type 1 diabetes mellitus (T1DM) in young children has increased considerably over recent years. The purpose was to examine the effectiveness and safety of continuous subcutaneous insulin infusion (CSII) therapy in preschool children with T1DM.A retrospective chart review of 113 children diagnosed with T1DM while younger than age 6 years. Mean age at diagnosis was 3.5±1.5 years and mean duration of follow 9.7±7.0 years. Patients were divided into 3 groups. Group1 initiated CSII therapy before the age of 6 years (n=26), Group 2 was treated with multiple daily injections (MDI) throughout follow-up (n=34), and Group 3 initiated CSII after age 6 (n=53). Metabolic control was assessed by HbA1C levels and safety by rates of severe hypoglycemia and diabetic ketoacidosis (DKA) events.In Group 1, the highest mean HbA1C value (8.5%) was observed 1–2 years prior to CSII initiation. During the 5 year period following CSII initiation, mean HbA1C levels ranged between 7.4 and 8.0%. Throughout the entire follow-up period, mean HbA1C levels were lower for Group 1 than Group 2 (p=0.05). In Group 3, mean HbA1C level decreased from 8.7% pre-CSII to 8.3% post-CSII (p<0.001). Nevertheless HbA1C levels remained higher than for those who started pump therapy before age 6 (p=0.02).Our study demonstrated better metabolic control in pre-school children treated with CSII compared to those treated with MDI. This benefit sustained for 5 years after CSII initiation and was not accompanied by increased risk of severe hypoglycemia or DKA events.
Keywords: type 1 diabetes; continuous subcutaneous insulin infusion; long term follow-up